Synthesis of novel [1,2,4]triazolo[1,5-b][1,2,4,5]tetrazines and investigation of their fungistatic activity - Korotina, Anna V.; Tolshchina, Svetlana G.; Ishmetova, Rashida I.; Evstigneeva, Natalya P.; Gerasimova, Natalya A.; Zilberberg, Natalya V.; Kungurov, Nikolay V.; Rusinov, Gennady L.; Chupakhin, Oleg N.; Charushin, Valery N. (Beilstein Journal of Organic Chemistry, 2022)
A series of novel [1,2,4]triazolo[1,5-b][1,2,4,5]tetrazines has been synthesized through oxidation reaction of the corresponding 3,6-disubstituted 1,2,4,5-tetrazines bearing amidine fragments. It is shown that the heterocyclic systems obtained can be modified easily at C(3) position in the reactions with aliphatic alcohols and amines. Also, the reactivity of [1,2,4]triazolo[1,5-b][1,2,4,5]tetrazines towards CH-active compounds has been studied. The obtained triazolo[1,5-b]annulated 1,2,4,5-tetrazines proved to be active in micromolar concentrations in vitro against filamentous anthropophilic and zooanthropophilic dermatophyte fungi (Trichophyton, Microsporum and Epidermofiton), which cause skin and its appendages (hair, nails) diseases.
Keywords: antifungal activity; nucleophilic substitution; oxidative cyclization; [1,2,4]triazolo[1,5-b][1,2,4,5]tetrazines

(untitled) - Lhassani, M.; Chavignon, O.; Chezal, J.-M.; Teulade, J.-C.; Chapat, J.-P.; Snoeck, R.; Andrei, G.; Balzarini, J.; De Clercq, E.; Gueiffier, A. (Eur. J. Med. Chem., 1999)

(untitled) - Rival, Y.; Grassy, G.; Michel, G. (Chem. Pharm. Bull., 1992)

(untitled) - Shawali, A. S.; Tawfik, N. M. (Arch. Pharmacal Res., 2009)

(untitled) - Altalbawy, F. M. A.; Darwish, E. S. S. (Asian J. Chem., 2011)

(untitled) - Hassan, B. A.; Naser, H. N.; Abdulridha, M. (Int. J. Res. Pharm. Sci. (Madurai, India), 2019)

(untitled) - El-Reedy, A. A. M.; Soliman, N. K. (Sci. Rep., 2020)

(untitled) - Maslov, D. A.; Korotina, A. V.; Shur, K. V.; Vatlin, A. A.; Bekker, O. B.; Tolshchina, S. G.; Ishmetova, R. I.; Ignatenko, N. K.; Rusinov, G. L.; Charushin, V. N.; Danilenko, V. N. (Eur. J. Med. Chem., 2019)

Russian Pat. - Bekker, O. B.; Danilenko, V. N.; Ishmetova, R. I.; Maslov, D. A.; Rusinov, G. L.; Tolshchina, S. G.; Charushin, V. N. (Substituted azolo[1,2,4,5]tetrazines – inhibitors of actinobacterial serine-threonine protein kinases, 2012)

Russian Pat. - Bekker, O. B.; Danilenko, V. N.; Ishmetova, R. I.; Korotina, A. V.; Maslov, D. A.; Rusinov, G. L.; Tolshchina, S. G.; Charushin, V. N. (Antituberculous therapeutic agent: composition of imidazo[1,2-b]tetrazine and pyrazinamide, 2015)

(untitled) - Kumar, H.; Chaudhary, R. P. (J. Chem. Pharm. Res., 2010)

(untitled) - Ishmetova, R. I.; Ignatenko, N. K.; Belyaninova, I. A.; Tolshchina, S. G.; Korotina, A. V.; Slepukhin, P. A.; Evstigneeva, N. P.; Zil’berberg, N. V.; Amineva, P. G.; Kungurov, N. V.; Rusinov, G. L.; Chupakhin, O. N. (Russ. Chem. Bull., 2015)

(untitled) - Ishmetova, R. I.; Ignatenko, N. K.; Korotina, A. V.; Ganebnykh, I. N.; Slepukhin, P. A.; Babkova, V. A.; Gerasimova, N. A.; Evstigneeva, N. P.; Zilberberg, N. V.; Kungurov, N. V.; Rusinov, G. L.; Spasov, A. A.; et al. (Russ. Chem. Bull., 2018)

Russian Pat. - Ishmetova, R. I.; Ignatenko, N. K.; Gerasimova, N. A.; Evstigneeva, N. P.; Zil’berberg, N. V.; Kungurov, N. V.; Rusinov, G. L.; Charushin, V. N.; Chupakhin, O. N. (3-Guanidino-6-R-triazolo[4,3-b][1,2,4,5]tetrazines with antibacterial activity, 2018)

Russian Pat. - Ishmetova, R. I.; Ignatenko, N. K.; Rusinov, G. L.; Charushin, V. N.; Spasov, A. A.; Petrov, V. I.; Sysoeva, V. A. (3-Guanidinoazolo[1,2,4,5]tetrazines having antiglycating activity and a process for their preparation, 2018)

(untitled) - Xu, F.; Yang, Z.-z.; Jiang, J.-r.; Pan, W.-g.; Yang, X.-l.; Wu, J.-y.; Zhu, Y.; Wang, J.; Shou, Q.-Y.; Wu, H.-g. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Shi, R.-J.; Yang, Z.-Z.; Gao, Y.-T.; Cai, W.-J.; Ye, C.; Xu, F.; Wang, J. (J. Chem. Res., 2019)

Russian Pat. - Bekker, O. B.; Danilenko, V. N.; Ignatenko, N. K.; Ishmetova, R. I.; Rusinov, G. L.; Tolshchina, S. G.; Charushin, V. N.; Shtil’, A. A. (6-Substituted 3-azolylimidazo[1,2-b][1,2,4,5]tetrazines showing anticancer activity, 2014)

Russian Pat. - Danilenko, V. N.; Charushin, V. N.; Rusinov, G. L.; Markova, A. A.; Ishmetova, R. I.; Abilev, S. K.; Ignatenko, N. K.; Tolshchina, S. G.; Rat’kin, A. V.; Shtil’, A. A. (Pharmaceutical composition based on 3-(4-methylimidazol-1-yl)imidazo[1,2-b][1,2,4,5]tetrazine as anti-tumor agent, 2017)

Progress in Heterocyclic Chemistry - Audebert, P.; Clavier, G.; Allain, C. (Triazines, Tetrazines, and Fused Ring Polyaza Systems, 2016)

Progress in Heterocyclic Chemistry - Audebert, P.; Clavier, G.; Allain, C. (Triazines, Tetrazines, and Fused Ring Polyaza Systems, 2017)

Progress in Heterocyclic Chemistry - Audebert, P.; Allain, C. (Triazines, Tetrazines, and Fused Ring Polyaza Systems, 2018)

Progress in Heterocyclic Chemistry - Hiebel, M.-A.; Suzenet, F. (Triazines, Tetrazines, and Fused Ring Polyaza Systems, 2020)

(untitled) - Chavez, D. E.; Parrish, D. A.; Mitchell, L.; Imler, G. H. (Angew. Chem., Int. Ed., 2017)

(untitled) - Man, T. T.; Wang, XK.; Zhang, J. G.; Niu, X. Q.; Zhang, T. L. (Cent. Eur. J. Energ. Mater., 2013)

(untitled) - Liu, L.; Jin, X.; Zhou, J.; Hu, B. (Int. J. Energy Res., 2021)

(untitled) - Clavier, G.; Audebert, P. (Chem. Rev., 2010)

(untitled) - Miomandre, F.; Audebert, P. (J. Photochem. Photobiol., C, 2020)

(untitled) - Lédée, F.; Audebert, P.; Trippé-Allard, G.; Galmiche, L.; Garrot, D.; Marrot, J.; Lauret, J.-S.; Deleporte, E.; Katan, C.; Even, J.; Quarti, C. (Mater. Horiz., 2021)

(untitled) - Tu, J.; Svatunek, D.; Parvez, S.; Liu, A. C.; Levandowski, B. J.; Eckvahl, H. J.; Peterson, R. T.; Houk, K. N.; Franzini, R. M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Wu, H.; Devaraj, N. K. (Acc. Chem. Res., 2018)

(untitled) - Mayer, S.; Lang, K. (Synthesis, 2017)

(untitled) - Chavez, D. E.; Hiskey, M. A. (J. Heterocycl. Chem., 1998)

(untitled) - Palysaeva, N. V.; Kumpan, K. P.; Struchkova, M. I.; Dalinger, I. L.; Kormanov, A. V.; Aleksandrova, N. S.; Chernyshev, V. M.; Pyreu, D. F.; Suponitsky, K. Y.; Sheremetev, A. B. (Org. Lett., 2014)

(untitled) - Xu, F.; Yang, Z.-z.; Ke, Z.-l.; Xi, L.-m.; Yan, Q.-d.; Yang, W.-q.; Zhu, L.-q.; Lin, F.-l.; Lv, W.-k.; Wu, H.-g.; Wang, J.; Li, H.-b. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Ishmetova, R. I.; Ganebnykh, I. N.; Ignatenko, N. K.; Tolshchina, S. G.; Korotina, A. V.; Eltsov, O. S.; Kravchenko, M. A.; Rusinov, G. L. (Russ. Chem. Bull., 2021)

(untitled) - Ganebnykh, I. N.; Tolshchina, S. G.; Ishmetova, R. I.; Ignatenko, N. K.; Slepukhin, P. A.; Rusinov, G. L.; Charushin, V. N. (Eur. J. Org. Chem., 2011)

(untitled) - Rusinov, G. L.; Ganebnykh, I. N.; Chupakhin, O. N. (Russ. J. Org. Chem., 1999)